Flat metal product and component made thereof
By forming specific textures on the surface of flat metal products, the problem of high wear and adhesion during molding is solved, lower wear and adhesion is achieved, and the wear resistance is improved. It is suitable for appearance and structural parts made in automobiles. .
Patent Information
- Application Number
- CN202380043961.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-05-23
- Publication Date
- 2025-01-10
AI Technical Summary
Existing flat metal products are prone to problems of wear and high adhesion during molding, resulting in component failure, especially in the case of zinc or aluminum-plated steel.
The specific texture is formed on the surface of flat metal products through flat rolling technology, ensuring that the average peak and valley height difference and the average distance to the valley edge are at least 18 μm2, and the texture design of repeated patterns is adopted, combined with laser structured methods, to form optimization The surface texture is to reduce wear and adhesion.
It significantly reduces the wear and adhesion of flat metal products during molding, improves surface wear resistance, extends the service life of components, and provides better appearance and performance in automobile manufacturing.
Smart Images

Figure CN119301291A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flat metal product and a component made thereof. Background Art
[0002] Sheet materials such as steel for the automotive industry are often coated with zinc-containing coatings, for example zinc coatings with particularly low aluminum contents from the melt (Z), zinc-based coatings with aluminum and magnesium contents from the melt (ZM), zinc coatings heat-treated after hot-dip coating or zinc-based coatings (ZF) and electroplated zinc coatings (ZE). Zinc protects the steel from corrosion as a so-called sacrificial anode. The coating applied to the flat metal product during production must withstand the loads during the forming process into a component. Wear can lead to scratches, pits and dents, or even to component failure. The wear characteristics of zinc or zinc-containing coatings are mainly influenced by the roughness of the sheet surface. Generally, forming aids, such as forming oils, are used during the forming process, the purpose of which is to prevent direct metal contact between the tool surface and the sheet surface. The surfaces slide against each other, and the projections on the surface of one contact partner rub against each other through the surface of the other contact partner, resulting in streak-like depressions. The longer the distance that the point load covers continuously on the surface, the more severe the streaks that may occur.
[0003] The roughness of the sheet metal surface can be varied, inter alia, by the choice of coating system and the application of a suitable texture.
[0004] Textures are usually applied to the surface of flat metal products by temper rolling. In temper rolling, two temper rolls are used in a temper rolling mill, in which the flat metal product is guided, so that the upper temper roll acts on the upper side of the flat metal product and the lower temper roll acts on the lower side of the flat metal product, and these rolls apply a corresponding texture to the surface of the flat metal product on both the upper and lower sides, depending on the structure of the temper rolls. The raised structures on the surface of the temper roll form depressions on the surface of the flat metal product, in other words, the raised structures on the surface of the temper roll form depressions on the surface of the flat metal product, in particular depending on the configuration of the structure and depending on the temper rolling system.
[0005] Skin-pass rolls can be produced by a random structuring process, usually by the so-called EDT process; see, for example, EP 2 006 037 B1.
[0006] The structures can be provided on the roller surface in a targeted manner by microlithography. For example, US Pat. No. 5,532,051 discloses circular and square structures which are produced by photolithography in a repeating sequence of a square grid on a roller and which can be transferred to the surface of a flat product during a rolling operation to improve the forming properties.
[0007] Publication DE 689 10 866 T2 also states that rectangular or hexagonal arrangements of cup-shaped depressions are advantageous for molding purposes, but are not optimal with regard to the paint appearance.
[0008] For example, see EP 2 892 663 B1, by laser beam bombardment, controlled structure creation can be achieved on the surface of the tempering roller in a defined arrangement, which is transferred to the flat product during tempering, and such tempered flat products can help improve the shaping and paint appearance.
[0009] The Moire effect can be avoided by a pseudo-random surface, see US 2019 / 0337032A1, in which circular protrusions with a diameter of 50-150 μm are arranged irregularly, with an overlap of less than 10% and a number dispersion of less than 20% per square millimeter.
[0010] Flat metal products can also be textured directly by laser bombardment, as described in WO 2017 / 125497 A1.
[0011] WO 2021 / 053088 A1 discloses such a surface in which the position of the depressions is varied by a random generator. A mathematical model is proposed, which can be generated by laser structuring a smoothing roll or directly laser texturing the sheet surface.
[0012] WO 2021 / 013938 A1 discloses a texture that can be created by direct laser texturing, which is designed to reduce or even avoid wear on the steel sheet to be coated and formed, and thus to reduce or even avoid adhesion on the tool surface in contact with the steel sheet. For this purpose, a prerequisite is that the material surface between the recesses has a very low radius on the flat metal sheet surface.
[0013] Surface failure phenomena due to wear and adhesion occur not only in the case of zinc-coated steel, in particular, but also in the case of aluminum-coated steel, in particular in the case of so-called indirect hot forming, and in the case of (uncoated) aluminum, since, depending on the alloy, the mechanical properties of aluminum differ only slightly from those of zinc, in particular with regard to strength.
[0014] Based on the prior art, it is therefore desirable to provide a temper-rolled flat metal product whose surface texture substantially results in only low or almost no wear during forming and has lower adhesion. Summary of the invention
[0015] A first teaching of the present invention relates to a temper-rolled flat metal product having a texture on the top and / or bottom surface of the flat metal product and having an average peak-to-valley height difference (d m-v ) and the average distance to the valley edge (r v), where d m-v and r v The product of is at least 18 μm 2 .
[0016] The texture is preferably in the form of depressions and webs arranged between the depressions, wherein the texture is based on a repeating pattern arranged in a grid. The texture comprises an average peak-to-valley height difference d m-v and the average distance to the valley edge r v For example, other characteristic values selected from the following group may also be included: arithmetic mean roughness Ra, peak number RPc, material content Mr, average distance to peak edge r v , and the maximum value of the peak radius r m,max and the maximum radius of the valley r v,max , and optional arithmetic mean waviness Wsa.
[0017] In the context of the present invention, it has been found that the characteristics of the surface flatness determine the tendency to wear. Surfaces with higher flatness resistance have lower wear.
[0018] According to DIN EN 10049:2014.03, characteristic roughness values such as the arithmetic mean roughness Ra and the number of peaks RPc should be measured outside the main grain direction in deterministic surfaces. In a hexagonal grid with a base direction of 30° or 60°, the recommended measuring direction is 45°±5° relative to the rolling direction. Since the hexagonal grid is invariant to a rotation of 60° and the measuring direction can be rotated by 90°, for integers m (m∈Z), a measuring direction of 15°+m·30° can also be used.
[0019] The same considerations regarding the measuring direction also apply to the waviness characteristic value Wsa, measured in accordance with SEP 1941. The roughness characteristic values Ra, RPc and Wsa can be determined by means of a tactile or contactless measuring system. The height value z(x) in the measuring length L should be centered:
[0020] ∫ 0 L z(x′)dx′=0
[0021] The arithmetic mean roughness Ra is:
[0022]
[0023] The material proportion Mr depends on the section c and is defined as:
[0024]
[0025] The peak value is the height value z(x) above the tangent line c=0, while the valley value is the value below the tangent line. The proportion of peaks in the surface morphology is Mr (0), referred to as M r ; The ratio of valley is (1-M r (0)), referred to as (1-M r ). The average height of the peak h m for:
[0026]
[0027] The average depth of the valley is t v for:
[0028]
[0029] Due to the centralization of the height value, it satisfies:
[0030] h m M r =t v (1-M r )
[0031] and
[0032] R a =h m M r +t v (1-M r )
[0033] Therefore, the average peak-to-valley height difference d can be calculated from Ra and Mr m-v :
[0034]
[0035] These characteristic variables and their interrelationships also apply to the height values z(x,y) measured by area. For example, a confocal microscope can be used to detect the surface topography by area, in particular at a lateral resolution of about 1.56 μm. The preferred measurement area is at least 1 mm 2 In case of curved metal sheets and large measurement areas, it may be necessary to remove some of the shape by standard filtering methods, e.g. using a filter with a limited wavelength λ C =1.0mm Gaussian filter. The topography data should be centered, in other words, the average value should be subtracted from the height value. The height value z(x,y) is represented by the point when z(x,y)≥0 on the peak. And in the valley it is the point when z(x,y)<0. The shortest distance between the peak and the valley point (x,y) is:
[0036]
[0037] When z(x,y)≥0.
[0038] The shortest distance from a valley to a peak point (x, y) is:
[0039] When z(x,y)<0.
[0040] The (maximum) inner radius of the maximum peak surface is:
[0041] r m_max =max(r m (x,y)),
[0042] and the (maximum) inner radius of the largest valley surface is:
[0043] r v_max =max(r v (x,y)).
[0044] The average value r in the measurement area F m is a measure of the fine structure of the peak
[0045]
[0046] and the mean value r v is a measure of the fine structure of the valley
[0047]
[0048] r m +r v The sum is inversely proportional to the peak number RPc.
[0049] A resist =r v ·d m-v
[0050] Characterized as surface wear resistance (A resist ) is the main measure of resist The higher the value, the more favorable the surface will be when molding.
[0051] Therefore, the wear resistance of the texture A resist At least 18μm 2 , in particular at least 20 μm 2 , preferably at least 22 μm 2 . A resist The value can be limited to no more than 200μm 2 , especially not more than 150μm 2 , preferably not more than 120 μm 2 , more preferably not more than 100 μm 2 .
[0052] “Flat metal products” refer to metal sheets or strips and other rolled products produced from a metal material, which can be a metal or a metal alloy. The metal or metal alloy preferably comes into consideration as steel or a steel alloy, or alternatively aluminum or an aluminum alloy.
[0053] The flat metal product surface is embossed with repeated depressions separated from each other by webs by the tempering operation. The depressions form liquid cavities for accommodating forming aids, such as forming oils, that promote forming. In order to better wet the webs with a sufficient amount of forming aids, it is particularly necessary to avoid too narrow a web width or rough peaks on the surface of the flat metal product. In combination with the geometry of the depressions, the shape of the webs between the depressions should make it more stable during the flattening process. The webs are preferably presented as a coherent area (i.e., platform-shaped), and are therefore connected to form a coherent web area. In this case, the friction characteristics are not only affected by the proportion of the web area, but also by its geometry, such as width and length. This is mainly because the stress consists of two parts that overlap each other. Normal compressive stress causes the surface to deform. In particular, the actual contact area between two rough surfaces usually accounts for only a few percent of the total area. Therefore, the pressure in local areas of the surface can be significantly higher than assumed considering the total contact area. Local pressure can lead to plastic surface changes. The larger the local contact area between the rough flat metal product surface and the tool surface, the smaller the local pressure acting on the microplane, which causes plastic deformation of the surface. This static stress is superimposed on the relative movement of the sheet plane (dynamic stress) during the forming process and can lead to pull marks. With increasing movement distance, these marks become more severe until undesirable surface scratches appear. Therefore, for example, the material area or the peak area fraction should not be too broad.
[0054] The texture on which the invention is based consists of repetitive shape elements arranged in a grid. The pitch of the basic grid is between 50 μm, in particular 70 μm, preferably 100 μm and 500 μm, in particular a maximum of 450 μm, preferably a maximum of 380 μm.
[0055] These form elements consist of a single depression which, in plan view, usually has an especially polygonal shape, such as a triangle, a quadrilateral or a hexagon, in particular an equilateral triangle or a regular hexagon.
[0056] Thus, a pattern comprising a plurality of adjacent individual depressions is repeated on the surface of the flat metal product, in particular in the temper rolling direction or perpendicular thereto. The axis of symmetry can be in the temper rolling direction or perpendicular thereto or rotated at a defined angle.
[0057] Use a tempering roller (pair) with a suitable structure, which can form the above-mentioned texture on one or both sides of the flat metal product after tempering. The surface of the tempering roller can be processed or structured by laser, especially short-pulse laser. Corresponding laser structuring methods and devices for implementing laser structuring methods are already known in the prior art, and in addition to EP 2 892 663 B1, they can also be seen in EP 3 172 006 B1 and EP 3 877 112 A1. In this way, a structure can be produced on the surface of the tempering roller, which, through laser bombardment, will lead to ablation of the surface material, that is, material removal in the area hit by the bombardment. Through targeted adjustment, the laser irradiation points can overlap or be spaced larger, so that an almost original state is retained between the laser irradiation areas. These areas not affected by the laser bombardment thus form one or more protrusions on the surface of the tempering roller. A complete transfer of the surface structure of the tempering roller to the surface of the flat metal product to be tempered is not possible in practice, but essentially only a significant part, for example the protruding parts of the surface profile of the tempering roller, will enter the surface of the flat metal product to be tempered and thus give the surface of the flat metal product after tempering a new appearance or characteristics that are different from the state before tempering. The tempering roller surface will form a surface texture on the surface of the selectively coated flat metal product with its protruding parts (positive mold) under the action of force, which will therefore only partially transfer corresponding depressions (negative mold) on the surface of the steel sheet or the surface of the selectively coated flat metal product.
[0058] The surface texture of flat metal products, whether coated or not, such as those meeting the following criteria:
[0059] an arithmetic mean roughness Ra of at least 0.50 μm, in particular at least 0.60 μm, preferably at least 0.70 μm, and a maximum of 5.0 μm, in particular a maximum of 4.0 μm, preferably a maximum of 3.0 μm;
[0060] - a peak number RPc of at least 30 1 / cm, in particular at least 40 1 / cm, preferably at least 50 1 / cm, and a maximum of 200 1 / cm, in particular a maximum of 150 1 / cm, preferably a maximum of 110 1 / cm, optimally a maximum of 90 1 / cm;
[0061] - the material proportion Mr is at least 30%, in particular at least 35%, preferably at least 40%, and a maximum of 65%, in particular a maximum of 60%, preferably a maximum of 57%;
[0062] - Average peak-to-valley height difference d m-v at least 1.0 μm, in particular at least 1.5 μm, and at most 8.0 μm, in particular at most 7.0 μm, preferably at most 5.5 μm;
[0063] - Maximum inner radius r of the peak m,max at least 14 μm, in particular at least 16 μm, preferably at least 18 μm, and at most 50 μm, in particular at most 40 μm, preferably at most 30 μm;
[0064] - Maximum inner radius of the valley r v,max at least 20 μm, in particular at least 25 μm, preferably at least 30 μm, and at most 100 μm, in particular at most 80 μm, preferably at most 70 μm;
[0065] - Average distance to the peak edge r m at least 4 μm, in particular at least 5 μm, preferably at least 6 μm, and at most 40 μm, in particular at most 30 μm, preferably at most 20 μm;
[0066] - average distance to the valley edge r v At least 4 μm, in particular at least 5 μm, preferably at least 6 μm, and at most 40 μm, in particular at most 30 μm, preferably at most 25 μm.
[0067] If the flat metal product according to the invention is used, for example, for exterior parts in automobile construction, the following additional criteria should also be taken into account: the arithmetic mean waviness Wsa>0 μm and in particular a maximum of 0.30 μm, preferably not more than 0.25 μm, more preferably not more than 0.20 μm, further preferably not more than 0.15 μm, and even more preferably not more than 0.13 μm.
[0068] In particular, even at higher roughness, the waviness generally remains small. The ratio of the arithmetic mean waviness Wsa to the arithmetic mean roughness Ra is preferably less than 0.3, more preferably less than 0.25, and particularly preferably less than 0.2.
[0069] The above criteria are to be regarded as average values for the bottom and / or top surface of the temper-rolled (coated) flat metal product, respectively.
[0070] The flat metal product according to the invention is a temper-rolled and / or straightened flat metal product.
[0071] The flat metal product according to the invention can be a steel sheet, which can be uncoated or coated. If the steel sheet is coated, the coating of the coated steel sheet has a metallic coating.
[0072] In one embodiment, the steel sheet is coated with a zinc-based coating applied by hot-dip galvanizing. In addition to zinc and unavoidable impurities, the coating may also contain additional elements, such as aluminum, with a content of up to 8% by weight, in particular up to 5% by weight, and / or magnesium, with a content of up to 8% by weight, in particular up to 5% by weight. Steel sheets with a zinc-based coating have very good cathodic corrosion protection, which has been used in the automotive industry for many years. If it is necessary to increase the corrosion resistance, the coating may additionally contain at least 0.3% by weight of magnesium, in particular at least 0.6% by weight, preferably at least 0.9% by weight. Aluminum can also be added together with or instead of magnesium, with a content of at least 0.1% by weight, in particular at least 0.3% by weight, in order, for example, to improve the bonding of the coating to the steel sheet, in particular to prevent iron in the steel sheet from diffusing into the coating during the heat treatment of the coated steel sheet, thereby ensuring, for example, good bonding properties. In this case, the thickness of the coating is generally between 1.5 and 30 μm per side, in particular between 2 and 20 μm per side, preferably between 3 and 15 μm per side. Below the minimum limit, sufficient cathodic corrosion protection may not be provided, while exceeding the maximum limit may cause joining problems during the connection of the steel plate according to the present invention or a component made therefrom with another component. In particular, if the coating thickness exceeds the maximum limit, the stability of the process may be affected during thermal joining or welding.
[0073] If the coating contains magnesium and aluminum in addition to zinc and unavoidable impurities, the coating or coating is referred to in the technical field as zinc-magnesium alloy, ZM or Zn—Al—Mg.
[0074] In a preferred variant, the aluminum content of the melt is from 1.1 to 8% by weight, in particular from 1.2 to 5% by weight.
[0075] In a preferred variant, the magnesium content of the melt is from 1.1 to 8% by weight, in particular from 1.2 to 5% by weight.
[0076] The coating can also contain only zinc and small amounts of aluminum in addition to unavoidable impurities, which is referred to in the professional field as a "Z" coating.
[0077] Inevitable impurities in the coating include, for example, silicon, antimony, lead, titanium, calcium, manganese, tin, cerium, lanthanum, chromium and other elements, the total content of which alone or in combination does not exceed 0.5% by weight, especially does not exceed 0.3% by weight.
[0078] When providing steel sheets with a metallic coating via hot-dip coating, temper rolling usually takes place after coating, ie the surface texture on the top and / or bottom side of the steel sheet is formed on the coated steel sheet.
[0079] In another embodiment, the steel sheet is coated with a zinc-based coating by galvanic coating. The thickness of the coating is 1.5 to 20 μm per side, in particular 2 to 15 μm per side, preferably 3 to 12 μm per side.
[0080] In another alternative embodiment, the steel sheet is coated with a zinc-based coating or an aluminum-based coating by PVD coating. The thickness of the coating is 1.5 to 20 μm per side, in particular 2 to 15 μm per side, preferably 3 to 12 μm per side.
[0081] When providing steel sheets with a metallic coating via galvanic coating or PVD coating, temper rolling is usually carried out prior to coating, ie the surface texture on the top and bottom sides of the steel sheet is produced on the uncoated steel sheet.
[0082] In another alternative embodiment, the steel sheet is coated with an aluminum-based coating, which may contain, in addition to aluminum and unavoidable impurities, up to 15% by weight of Si, optionally up to 4% by weight of Fe, optionally up to 1.0% by weight of alkali metals or alkaline earth metals.
[0083] In a preferred variant, the silicon content is from 0.2 to 4.5% by weight, or from 7 to 13% by weight, in particular from 8 to 11% by weight.
[0084] In a preferred variant, the iron content is from 0.2 to 4.5% by weight, in particular from 1 to 4% by weight, preferably from 1.5 to 3.5% by weight.
[0085] In a preferred variant, the optional content of alkali metal or alkaline earth metal comprises 0.01 to 1.0 wt. % magnesium, in particular 0.1 to 0.7 wt. % magnesium, preferably 0.1 to 0.5 wt. % magnesium. In addition, the optional content of alkali metal or alkaline earth metal can also contain in particular at least 0.0015 wt. % calcium.
[0086] In another alternative embodiment, the steel sheet is coated with an aluminum-based coating. In this case, the coating may contain, in addition to aluminum and unavoidable impurities, 2 to 24% by weight of zinc, 1 to 7% by weight of silicon, and optionally 1 to 8% by weight of magnesium if the silicon content is between 1 and 4% by weight, and optionally also lead, nickel, zirconium or hafnium in a total amount of not more than 0.3% by weight.
[0087] Unavoidable impurities in the coating may include, for example, elements from the group consisting of antimony, lead, titanium, manganese, tin, lanthanum, cerium and chromium, either alone or in combination, in a total content of up to 0.5% by weight, in particular not more than 0.3% by weight.
[0088] Sheet steel consists of steel which, in addition to iron and unavoidable impurities, also contains alloying elements such as carbon, silicon, manganese and aluminium, where, depending on the application and strength class, other components may also be present, either alone or in combination, such as titanium, chromium, boron etc. Experts know which steels are suitable for the production of cold-formed and indirectly hot-formed components, depending on the application, in particular in automotive construction.
[0089] Alternatively, the (temper-rolled) flat metal product can also be an aluminium sheet.
[0090] According to a second teaching, the invention relates to a component produced by cold forming from a flat metal product made of the steel / steel alloy or aluminium / aluminium alloy according to the invention.
[0091] The component may be an exterior skin part for automobile manufacturing. Thus, the exterior skin part may be used for moving parts, such as doors and hatches, but also for roofs, fenders, etc. Alternatively, the component may also be a structural component for automobile manufacturing. It is also conceivable to use it in the chassis field.
[0092] According to a third teaching, the invention also relates to a component produced from a flat metal product made of the steel / steel alloy according to the invention by indirect hot forming.
[0093] The component may be a structural component used in automobile construction. Structural components are therefore part of the vehicle body, such as pillars (B-pillars), longitudinal beams and cross beams (including shock absorbers).
[0094] In one embodiment of the component according to the invention, the component is already painted.
[0095] The temper-rolled flat metal products according to the invention have advantages in terms of forming compared to the prior art. Evidence for this is provided by the so-called multi-friction test (MFT). Different steel sheets (gap-free steel IF, bake-hardened steel BH and dual-phase steel DP) with a thickness of 0.6 mm to 0.7 mm were coated with different hot-dip coating layers (Z and ZM) with a coating thickness of 7 μm on each side and then temper-rolled on both sides with temper-rolling rollers of different structures at a temper-rolling reduction of 1% to 1.5%. The surface textures produced on the coated steel sheets using the different temper-rolling rollers had, on average, the characteristic values shown in Table 1.
[0096] The surfaces of samples 1 to 6 correspond to the prior art. Sample 1 (IF with Z) and sample 2 (BH with Z) have a random texture obtained according to the technology of EP 2 006 037 B1, in which the surface of the tempered roll is processed by the EDT texturing method and subsequent superfinishing (SF). Sample 3 (BH with ZM) uses an EDT tempered roll without SF.
[0097] Samples 4 (IF with Z), 5 (DP with Z) and 6 (BH with ZM) have a deterministic texture in the form of a checkerboard pattern, wherein the smooth roll surface is produced by a pulsed laser texturing method according to the technique of EP 2 892 663 B1.
[0098]
[0099]
[0100] Table 1
[0101] Sample 7 (IF with Z), Sample 8 (DP with Z), and Sample 9 (BH with Z) have a repeating pattern of a "triangle" texture obtained according to the teachings of the present invention.
[0102] Sample 10 (IF with Z), Sample 11 (DP with Z), and Sample 12 (BH with Z) have a repeating pattern of a "trapezoidal" texture obtained in accordance with the teachings of the present invention.
[0103] Sample 13 (IF with Z), Sample 14 (DP with Z), Sample 15 (BH with Z), and Sample 16 (DP with ZM) have a repeating pattern of a "hexagonal" texture obtained according to the teachings of the present invention.
[0104] MFT, also known as the Renault test, is a commonly used test method for surface wear characteristics. According to the "Renault D31 1738 / C" test method, a strip sample of the material to be tested is repeatedly pulled through a flat and circular friction fixture with a diameter of 20mm. The tool kit is made of 1.3342 material with a hardness of >60HRC and a grinding roughness of Ra of 0.1μm. Since the contact is linear, the circular friction fixture allows a higher contact pressure on the sample surface. In the test procedure, each sample 1 to 10 is cut into five 700x 50mm 2 The strip samples were cleaned, degreased, and lubricated with PL 3802S at 1.5 g / m 2 Each sample strip is clamped to the clamping device in turn and pulled through two friction clamps, with a test distance of 50 mm. The test speed is 5 mm / s, and the extrusion force or normal force F N The value is kept constant at 5 kN throughout the test. During the test, the required tensile force F is recorded at a recording rate of 10 Hz. D Each strip was pulled five times over the same location without cleaning the tool or strip each time. After the five strips had passed through the tool five times, the tool was evaluated for wear and tear.
[0105] Friction coefficient
[0106] μ (n) =F D / 2F N
[0107] In the nth pull, the friction coefficient is determined as an average value on each sample. In the first pull, the friction coefficient μ 1 It fluctuates slightly between 0.11 and 0.14 and is independent of the zinc coating made from the melt (Z or ZM). In the case of the same texture (EDT, Double I, etc.), the variants with higher roughness (see Ra values in Table 1) have a higher friction coefficient (see Table 2).
[0108] In the fifth pull, the difference in the friction coefficient μ5 is more obvious, with values ranging from 0.08 to 0.21. The higher the arithmetic mean roughness Ra, the lower the value of the friction coefficient μ of the corresponding texture, as shown in Table 2.
[0109] For the samples with the prior art Z coating (Double I or EDT), the friction coefficient continues to increase at the latest after the second pull. With these textures, the use of the ZM coating alone already leads to continuously decreasing values of the friction coefficient μ.
[0110] Sample No. Texture coating <![CDATA[μ 1 ]]> <![CDATA[μ 2 ]]> <![CDATA[μ 3 ]]> <![CDATA[μ 4 ]]> <![CDATA[μ 5 ]]> The present invention 1 EDT Z 0.129 0.145 0.165 0.188 0.195 - 2 EDT Z 0.140 0.140 0.158 0.183 0.206 - 3 EDT ZM 0.140 0.125 0.120 0.100 0.098 - 4 Double I Z 0.119 0.127 0.159 0.181 0.205 - 5 Double I Z 0.144 0.126 0.134 0.156 0.178 - 6 Double I ZM 0.120 0.085 0.084 0.082 0.082 - 7 triangle Z 0.119 0.107 0.101 0.099 0.095 + 8 triangle Z 0.143 0.136 0.12 0.107 0.101 + 9 triangle Z 0.135 0.110 0.092 0.086 0.084 + 10 Trapezoid Z 0.109 0.107 0.107 0.108 0.115 + 11 Trapezoid Z 0.139 0.128 0.115 0.108 0.100 + 12 Trapezoid Z 0.131 0.118 0.119 0.113 0.108 + 13 hexagon Z 0.113 0.111 0.12 0.136 0.151 + 14 hexagon Z 0.132 0.119 0.109 0.101 0.098 + 15 hexagon Z 0.135 0.119 0.117 0.116 0.111 + 16 hexagon ZM 0.119 0.100 0.085 0.076 0.078 +
[0111] Table 2
[0112] The surface of the invention can reduce the increase in friction. In particular, the surface with the "triangular" texture, although the coating is a zinc coating (Z) from the melt, the friction is continuously reduced during each pull process.
[0113] Tests have shown that in addition to the coating, the texture of the sheet surface can also have a significant impact on the friction of coated flat metal products.
[0114] Therefore, to analyze the surface changes, the surfaces of different strips in the MFT test were examined by confocal microscopy before the first pull, after the third pull, and after the fifth pull. DETAILED DESCRIPTION
[0115] Figure 1 The surfaces coated with molten zinc (Z) coating were compared with the unpulled surfaces after the third and fifth pulls. It can be clearly seen that in the case of the "double I" texture, the original texture is no longer obvious after the third pull. In the case of the "EDT" texture, some relatively coarse depressions still exist, which can serve as lubrication grooves and accommodate wear particles. After further stress, deeper grooves or scratches are formed on the surface.
[0116] In contrast, surfaces coated with a zinc-based cladding (ZM) made from a melt with aluminum and magnesium additions showed very high wear resistance in the MFT test. In all texture types, even in the case of the "EDT" and "double I" textures, these structures did not completely disappear after the fifth pull and no scratches were formed.
[0117] Embodiments of the invention show significantly higher wear resistance and thus have significant advantages over surfaces (coatings) that themselves have a significant wear tendency. This performance has been demonstrated on aluminum-coated steel sheets and aluminum sheets as flat metal products, where the surface texture according to the invention also performs better than the "EDT" and "Double I" textures.
[0118] The substantially rough surface will level out laterally by contact with the smooth tool surface, thus providing a larger reserve of lubricant, which helps to reduce friction and reduce cold welding that occurs on the tool surface in contact with the sheet during the forming process.
[0119] It was found that textures with greater depth and their larger cross-sections of depressions were able to remain in contact with the tool longer.
[0120] A resist =r v ·d m-v
[0121] It should be as large as possible so that the surface can resist being completely flat, thus favoring the avoidance of sticking or abrasion.
[0122] The texture pattern does not necessarily have to be a triangular or hexagonal design, or a corresponding equivalent contour such as an inner six circles or a cloverleaf shape, but can also be a polygonal shape with multiple vertices as long as the geometric requirements of the surface texture of the present invention are followed.
[0123] Figure 2 The friction coefficient μ5 and the characteristic variable A are shown in the fifth pull of MFT. resist , that is, the peak-to-valley height difference d m-v and the average distance to the valley edge r v The product of (see the eigenvalues in Tables 1 and 2) for the variation of Z and ZM. For each point in the coordinate system, a polygonal line has been determined for Z and a straight line has been fitted for ZM.
[0124] Figure 3 and Figure 4 Two exemplary texture patterns are used as examples to illustrate the method for determining the eigenvalue r m or v and r m,max or v,max The geometric relationship of the "triangle" texture A Figure 3 and "hexagon" texture A Figure 4 .like Figure 3 and Figure 4 As shown, the eigenvalue r m,max is the inner radius of the maximum peak, that is, the maximum inner radius of the peak, corresponding to the maximum distance between two depressions (A). v,max is the inner radius of the largest valley, which is actually the maximum inner radius of the valley. m or v denote the average distance to the peak edges and valley edges, respectively, in particular in the measured area under investigation. The texture is based on a repetitive pattern, and therefore a deterministic pattern, which is arranged in a grid R. The base grid R consists of hexagonal shapes (see Figure 3 and Figure 4 ), whose side length S is in the range of 50 μm to 500 μm. M is the centroid / center of each depression A. The webs are arranged between the depressions A, or the webs separate the individual depressions A from each other. The width of the webs is variable in the longitudinal direction, ranging from >0 μm to r m,max The arrows indicate the direction of the smoothing roll.
[0125] exist Figure 5 In the example of the surface of a temper-rolled flat metal product, the design essentially corresponds to hexagonal depressions A, but due to the action of the laser in structuring the temper-rolling roll, this design cannot be seen in the form of straight lines, but rather consists of overlapping laser pulses, resulting in a pattern similar to a hexagonal circle or Torx texture, see Figure 1 In this example, the measured texture depth is 3.89 μm, the arithmetic mean roughness Ra is 0.95 μm, the peak number RPc is 67 1 / cm, and the arithmetic mean waviness Wsa is 0.08 μm. Material ratio M r The resulting peak-to-valley height difference d m-v The maximum inner radius of the peak is 1.98 μm. m,max is 21.9 μm, and the maximum inner radius of the valley is r v,max The average distance to the peak edge is 51.2 μm. m is 7.5 μm, and the average distance to the valley edge is r v is 15.7 μm, which is about one-third of the maximum inner radius. The triangular texture is closer to the clover texture; see Figure 1 The triangle in .
Claims
1. A flat metal product having a texture on the upper surface and / or the lower surface of the flat metal product, the texture having an average peak-to-valley height difference d m-v and the average distance to the valley edge r v , characterized in that, d m-v and r v The product of is at least 18 μm 2 .
2. The flat metal product according to claim 1, the texture consisting of depressions (A) and webs arranged between the depressions (A), wherein the texture is based on a repeating pattern arranged in a grid (R).
3. The flat metal product according to any one of the preceding claims, wherein the arithmetic mean roughness Ra of the texture is between at least 0.50 μm and at most 5.0 μm.
4. The flat metal product according to any one of the preceding claims, wherein the peak number RPc of the texture is between at least 30 1 / cm and at most 200 1 / cm.
5. The flat metal product according to claim 1, wherein the average distance r of the texture to the valley edge is v Between at least 4 μm and at most 40 μm.
6. The flat metal product according to any one of the preceding claims, wherein the average distance r of the texture to the peak edge is m Between at least 4 μm and at most 40 μm.
7. The flat metal product according to any one of the preceding claims, wherein the flat metal product is a steel sheet and is provided with a metal coating.
8. The flat metal product according to any one of claims 1 to 6, wherein the flat metal product is an aluminium sheet.
9. The flat metal product according to claim 7, wherein the steel sheet is coated with a zinc-based coating applied by hot-dip galvanizing.
10. The flat metal product according to claim 7, wherein the steel sheet is coated with a zinc-based coating applied by electroplating.
11. The flat metal product according to claim 7, wherein the steel sheet is coated with a zinc-based or aluminum-based coating applied by physical vapor deposition.
12. The flat metal product according to claim 7, wherein the steel sheet is coated with an aluminum-based coating applied by hot-dip galvanizing. 13 . The flat metal product as claimed in claim 1 , wherein an arithmetic mean waviness Wsa of >0 μm and a maximum of 0.30 μm is taken into account as a further characteristic value.
14. A component produced by cold forming a flat metal product as claimed in any one of claims 1 to 11.
15. The component of claim 14, wherein the component is an outer skin component.
16. A component produced by hot forming the steel sheet of claim 1, 7 or 12.
17. The component of claim 14, wherein the component is a structural member.
18. A component according to any one of claims 14 to 17, wherein the component is painted.
Citation Information
Patent Citations
Method and apparatus for forming a micro-pattern on the surface of a roll, metal sheets for presswork manufactured by the roll and method of manufacturing.
DE68910866T2
Flat product made of a metallic substance, in particular a steel substance, use of such a flat product and roller and method for manufacturing such a flat product
EP2006037B1
Flat product made of metal material, in particular a steel material, use of such a flat product, and roll and method for producing such flat products
EP2892663B1
Method for structuring a roller by means of laser removal
EP3172006B1
Apparatus and method for structuring a roller surface
EP3877112A1